Perancangan Sistem Pendukung Keputusan Untuk Pemilihan Lokasi Dalam Perluasan Usaha Kafe menggunakan Analytical Hierarchy Process - Wowon Priatna; Suryadi (Ikatan Ahli Informatika Indonesia (IAII), 2019)
vanilla. The Milk Café was founded in 2015 which currently has 3 branches and 5 franchises in various cities in Central Java and D.I. Yogyakarta and many more. the milk café owner has plans to open a new café branch. The milk café owner does not yet have the right method for determining location selection recommendations. Currently, café owners only conduct surveys and then choose locations that they think are appropriate based on several criteria so that café owners are often hesitant in determining the right location. Choosing an improper business location can cause bankruptcy or failure to run a business. This study aims to find out how the AHP method is able to provide problem solving solutions in the selection of locations in the expansion of the café business. And how to build a decision support system application AHP method. The data used are location data to conduct a feasibility survey based on criteria data to locations that have been determined by the team leader, where the criteria for determining new cafes are strategic locations, market share, competitors, rental prices and area size ... results from AHP calculations for expansion of the café is that it can be concluded that the alternative location of Jl. Sultan Syahrir Surakarta was stated as the most suitable location to be chosen as the location of the new branch of The Milk Café with the highest weighting value of 0.235. While the least recommended alternative locations are Jl. Adi Soemarmo with the least total weight is 0.153.